2022
DOI: 10.3390/biomedicines10020369
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Inhaled Nitric Oxide Therapy in COVID-19 Patients

Abstract: The global COVID-19 pandemic has become the largest public health challenge of recent years. The incidence of COVID-19-related acute hypoxemic respiratory failure (AHRF) occurs in up to 15% of hospitalized patients. Antiviral drugs currently available to clinicians have little to no effect on mortality, length of in-hospital stay, the need for mechanical ventilation, or long-term effects. Inhaled nitric oxide (iNO) administration is a promising new non-standard approach to directly treat viral burden while enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 164 publications
(198 reference statements)
0
31
0
2
Order By: Relevance
“…[25][26][27] Due to its role in reducing ventilation-perfusion mismatching, iNO is used as a rescue therapy for hypoxemia in intubated and mechanically ventilated patients with hypoxic respiratory failure, both from COVID-19 and not. 8 Maternal hypoxemia is associated with an increased risk of miscarriage and fetal demise; thus, the Society for Maternal-Fetal Medicine COVID-19 task force recommends prompt reversal of hypoxemia and maintenance of an oxygen saturation greater than 95% in pregnant patients. 6 In a previous study, iNO was delivered to six nonintubated pregnant patients with severe COVID-19 pneumonia with the intent of increasing oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Due to its role in reducing ventilation-perfusion mismatching, iNO is used as a rescue therapy for hypoxemia in intubated and mechanically ventilated patients with hypoxic respiratory failure, both from COVID-19 and not. 8 Maternal hypoxemia is associated with an increased risk of miscarriage and fetal demise; thus, the Society for Maternal-Fetal Medicine COVID-19 task force recommends prompt reversal of hypoxemia and maintenance of an oxygen saturation greater than 95% in pregnant patients. 6 In a previous study, iNO was delivered to six nonintubated pregnant patients with severe COVID-19 pneumonia with the intent of increasing oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2’s tropism for endothelial cells leads to cell apoptosis, and thus a decrease in endothelial NO production [ 3 , 91 ]. Inhaled NO might be a therapeutic option in COVID-19 [ 92 ]. Inhaled NO has proven pulmonary vasodilation activity.…”
Section: Covid-19 Treatments That Target the Endothelium Or Endotheli...mentioning
confidence: 99%
“…In vitro experiments have demonstrated that NO has antiviral activity against SARS-CoV-2 [ 93 ]. Although the modalities of inhaled NO administration (particularly the timing) still need to be explored, early initiation of this treatment might be promising [ 92 ].…”
Section: Covid-19 Treatments That Target the Endothelium Or Endotheli...mentioning
confidence: 99%
“…However, the lack of a larger clinical trial with patient-centered outcome as the primary endpoint precludes any further conclusion concerning iNO treatment in this patient population. More recently, due to the dramatic impact of the SARS-CoV-2 pandemic on the health system, several case series reported data on the treatment with iNO in patients with coronavirus disease 2019 (COVID-19) [ 77 ]. In all these studies, high-dose iNO (160–200 ppm) was delivered with intermittent regimens for 30 min per session twice daily.…”
Section: High-dose Exogenous No As An Antimicrobial Treatmentmentioning
confidence: 99%